Fiqih Muamalah Sebagai Solusi Dalam Menghadapi Praktik Riba dan Gharar - Fikri Ibnu Fazda; Fadil; Fatmah Taufik Hidayat (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Fiqh Muamalah, as an essential branch of Islamic jurisprudence, provides ethical and legal guidelines for economic activities, especially in addressing practices that contradict Islamic principles, such as riba (usurious interest) and gharar (uncertainty in transactions). These concepts are prohibited in Islam due to their exploitative and unjust nature. This article explores how fiqh muamalah can serve as an effective solution in minimizing and even eliminating such practices by establishing a foundation for fair, transparent, and non-exploitative transactions. Through a normative approach and analysis of contemporary financial practices, the article highlights the significance of Sharia-compliant contracts, such as murabaha, mudarabah, and musharakah, in avoiding riba and gharar. This study also emphasizes the need for a deep understanding of fiqh muamalah principles, enabling individuals to conduct economic activities in accordance with Sharia, fostering a fair and sustainable economy. Thus, fiqh muamalah is not only relevant as a legal guide but also serves as an ethical tool for economic development within the Muslim community.